Communication of News Contributor Organizations at Diskominfo Agencies of Nunukan Regency - Asa Zumara; Sukriansyah S Latief; Yusmanizar Yusmanizar (Newinera Publisher, 2024)
The Communication, Informatics, Statistics and Coding Office of Nunukan Regency has the task and function of serving information and disseminating development information in Nunukan Regency. As the leading sector disseminator of information, the Department of Communication and Information and Coding cooperates with all Regional Apparatus Organizations (OPD) as contributors to news and information. The information distribution channel is called SIMP4TIK. Of the 30 OPD contributors, only 14 contributors wrote on the SIMP4TIK news portal in quarters 1 and 2. Organizational communication plays an important role in the realization of organizational goals. This study aims to analyze how effective the communication of news contributor organizations in Nunukan Regency government agencies and what are the factors that influence it. The theory used is organizational communication theory. The research method used is descriptive qualitative with the object of research of the publication team consisting of team leaders, editors and OPD contributors in Nunukan Regency. The results of this research were obtained through interviews, observations, and literature studies. The results of the study found that organizational communication has not run optimally on news contributors in the Nunukan Regency Government. The triggering factors include OPD contributors having many tasks besides writing news. Another result, OPD contributors find it difficult to upload news due to lack of knowledge about technology and lack of interest in news authorship. On the editor's side, the lack of intensity of editorial meetings and communication between editors is a factor in the ineffectiveness of organizational communication.